Breeding design thinkers - Abd Rahman, Khairul Aidil Azlin (Universiti Putra Malaysia Press, 2016)
Knowledge comes before action and there can be no action without knowledge. Knowledge is worthless except, when they are passed into action” (Al-Quran; Muhammad 47:19). With the existing knowledge, it is a state of being active; the action will be transformed into new knowledge. By doing things, the body goes through the process of learning. This process of drilling the mind with repetitive exercises will internalize the action in the body. Therefore, there will be knowledge, experience and skills. Interaction activities with human and human, human and man-made things, human and nature spark out new knowledge that is by learning the existence and how it was created. By doing this, the sense of awareness derives ideas to imitate, improve or create a new one. If we learn from man-made things, it is just an improvement, but if it is learned from nature and the environment created by God, it will be novel!